A decisão interlocutória inaudita altera parte: entre legitimidade e efetividade - Rafael Augusto de Morais Andrade (2014)
The Brazilian civil process, within the litigation, in cases in which the plaintiff asks for effective legal protection of urgency about the disputed object, allows the judge to utter interlocutory decision without hearing the defendant, in situations where according to the legal requirements, subjectives and objectives, there is a risk of irreparable harm to the plaintiff, or a hard harm. What justifies and therefore legitimizes the solitary decision of the judge, without the immediate opportunity to contradictory to the litigators, is the mismatch between the time and the form for the manifestation of the defendant and on the other hand, the safety of the legal asset in litigation, as a precaution to ensuring the effectivity of the final decision, or also as a way to satisfaction of a right to interrupt or prevent, in favor of the plaintiff, the risk of irreparable harm to the plaintiff, or a hard harm. However, over a long time and many theoretical constructs - especially about the constitutional nature of the process - we made a choice of a suitable process to democracy, in which citizens could, through the expression of their opinions, the exercise of their rights and legal satisfaction of their wants, with responsibility, define their way of life and destiny. In this context, an arbitrary decision, which impose to the litigants in the process the volition of an third person who is alien to their consciences, may conflict with the exercise of those in the process of their fundamental due process rights, contradictory, full efense and equality, to culminate in the obstruction of the democracy within one of the republican powers. Moreover, in urgency situations, provide to the defendant the form and the time designed to his manifestation, and more than that, to his integration into the process by the full exercise of their rights to full defense, to contradictory and equality, may imply the impossibility of the right of action of the plaintiff, also essential, as well as the obliteration of the object of action whose right is exercised. While it is notorious the procedural dilemma currently faced by the subjects of the process, between ensure one or another fundamental right - has long overcome by the doctrine in favor of the plaintiff - the possibility of simultaneous and effective guarantee of the right of action of the plaintiff, the litigators right to contradictory, full defense and equality, and to the material right in dispute, implies in flagrant violation of due process when uttered interlocutory decisions without hearing the defendant.